Penguatan Peran Komisi Yudisial dalam Penegakan Hukum di Indonesia - Bambang Sutiyoso (Fakultas Hukum Universitas Islam Indonesia, 2011)
The role of Judicial Commission in enforcing law has not been optimal, especially in conducting its function and authority to conduct external supervision of judges. The problem addressed in this research is what effort should be done to strengthen the role of Judicial Commission for law enforcement in Indonesia. The approach used in this research is juridical normative, and data source in this research is secondary data, which are primary, secondary, tertiary law material. Furthermore, the law material is analyzed descriptively and qualitatively. The research result shows that Judicial Commission needs to strengthen its role in enforcing law through the effort in: a. accelerating the revision of responsive and visionary Law of Judicial Commission; b. strengthening the role of institutional; c. strengthening institution in conducting external supervision, both preventively and repressively; d. reforming regulation in the field of justice in order to harmonize and synchronize the laws of Judicial Power, Supreme Court, Constitutional Court and the Judicial Commission; and e. strengthening and arranging its organization and personnel.Key words : Judicial commission, law enforcement, supervision of judge